Predicting Apple Yield Losses as Influenced by Weather Driven Time of Arrival of Phenological Stages and Soil Quality in Temperate Regions of North-West Himalayas - Rakesh Mohan Datt; Vinay Kukreja; Anil Sharma; Kishan Lal Kumawat (Journal of the Indian Society of Soil Science, 2023)
The present investigation was carried out to predict the time of arrival of important phenological stages of apple and their effect on fruit yield. The yield losses in relation to soil quality index (SQI) were calculated and an empirical model to calculate these losses on the basis of relative SQI was developed. This is one of the research areas for agriculture. The data relating to the arrival of weather governed the phenological stage, its variation from referred date of arrival (RDA) (±3 days) and further effect on yield was studied and used to predict potential yield losses. It was observed that variation in time of arrival of phenological stage, from RDA, does have its effect on fruit yield that declined between 29.8 to 41.5% under different climatic scenarios, due to advancement in their arrival. This variation was negatively but significantly related to weather parameters like average temperature and temperature difference with values of correlation coefficient ranging between r = -0.70** to r = -0.95** and was having nonsignificant relation with rainfall (r = 0.38). The output of the investigation reveals that if the arrival of various phenological stages of apple is predicted precisely, its negative effect can be managed.